Analysing the Adoption of awesome South Africa mobile travel application as a marketing strategy - Chivizhe, Takunda Victor (School of Management Studies, 2020)
Mobile Marketing is a critical marketing strategy and a foundation of competitive advantage for small to medium enterprises in the tourism and hospitality industry in South Africa. While many studies focus on mobile marketing, this study focuses on the adoption of mobile marketing innovations by small to medium enterprises in the tourism and hospitality industry in the Western Cape Province of South Africa. Analysing the adoption of Awesome South Africa mobile application, as a marketing strategy among SMEs in the Western Cape tourism and hospitality industry was therefore imperative to understand the factors that influence mobile marketing adoption. The objective was to find out the factors that contribute to the adoption of mobile marketing as well as the factors that would impede the adoption of mobile marketing by the SMEs in this industry. The research employed the Technology Acceptance Model as a theoretical framework as well as a guide in ascertaining the factors that affect the adoption of mobile marketing innovations among SMEs. There is certainty that the Awesome South Africa mobile travel application could partly solve the information asymmetry problem as well as the marketing challenges of the SMEs in the Western Cape Tourism and hospitality industry. An exploratory design was deployed in this study, resulting in the application of a qualitative research approach for data collection, analysis and interpretation. Both content and thematic data analyses were used in this study because data was collected from multiple sources that included reports and face-toface interviews. The research findings showed that the TAM provides a reasonable explanation of the factors that influence technology acceptance amongst SMEs. Perceived usefulness, perceived cost, perceived competitive pressure and perceived employee capability emerged as the significant factors that simultaneously influenced mobile marketing adoption among SMEs. Factors impeding the adoption of mobile marketing application by the SMEs included perceived high cost of adoption, lack of managerial support, employee incompetence, limited financial resources and perceived complexity of the mobile marketing innovations. The recommendation was that the Awesome South Africa mobile application innovators should capitalise on the TAM constructs in order to realise the adoption of their mobile application among SMEs in the Western Cape tourism and hospitality industry.